From center stage to backdrop: thematization and generic news frames of the extended pandemic in Argentine digital newspapers - Gomez Wagner, Celeste (2023)
If there is one thing we can be sure about the COVID-19 pandemic, it is that it caused an irruption of such magnitude throughout the world that the resonances of the multiple and varied changes it generated have yet to be seen. In relation to communication processes, the demand for information in real time increased and the media took center stage, especially in an initial period when the possibilities of intersubjective contrasts between people were diminished by the confinements. But this was not a constant: as the pandemic spread over time, it lost its novelty character and went from center stage to backdrop in media coverage. This research describes the thematic shifts and the predominant frames that La Nación, Clarín (in its digital versions) and Infobae deployed in their coverage of the pandemic between 2020 and 2022. Framed in the contributions of the agenda setting and framing theories, this paper starts with a quantitative content analysis and compares four specific time frames (April 2020, October 2020, May 2021 and January 2022), chosen for having represented significant peaks in the development of the pandemic in national health terms. The analysis shows that the concentration of the health issue, as well as the prominence of the variables that make up the morality and human interest frames were diluted over time, making the frames in the coverage of the issue less compact and more dispersed.